The use of non‐invasive ventilation in very old patients with hypercapnic acute respiratory failure because of COPD exacerbation. Issue 12 (4th October 2014) - Nicolini, A.; Santo, M.; Ferrera, L.; Ferrari‐Bravo, M.; Barlascini, C.; Perazzo, A.
Summary: Aims: We prospectively enrolled 207 patients (121 were 75 or older and 86 younger than 75) who were admitted to three Respiratory Monitoring Units. The primary outcomes were intubation and mortality rates; the secondary outcomes were changes in arterial blood gases analysis, non‐invasive ventilation (NIV) duration and length of hospital stay. Results: Hospital mortality was similar in the two groups, as were intubation rates. The proportion who died in the very old patient group was 19.8% (24/121) vs. 10.4% (9/86) in the younger group. Intubation rate was 10.7% (13/121) in the very old patient group and 11.6% (10/86) in the younger group. The presence of comorbidities, the severity of illness (SAPS II), the level of consciousness, NIV failure (intubation), absolute value of pH prior to NIV, as well as the changes in pH and paCO2 and PaO2 /FiO2 after 2 h of NIV, were the variables associated with higher mortality. Very old patients had significantly higher NIV duration than younger patients (69.0 ± 47.0 vs. 57.0 ± 27.0 h) (p ≤ 0.03) and hospital stays (11.6 ± 3.8 vs. 8.4 ± 1.4) (p ≤ 0.02). Conclusions: The use of NIV in very old patients was effective in many cases. Endotracheal intubation after NIV failure was not efficacious in either group.